TYPES OF SHELTERS FOR HOMELESS PEOPLE - Martynenko, Volodymyr; Obynochna, Zoriana (Theory and practice of design, 2023)
This article highlights key aspects of forming shelters for the homeless with a focus on rehabilitation, socialization, and reintegration of this vulnerable population. The article identifies that a shift from permanent shelters, oriented towards entrenched homelessness, to various forms of temporary housing may be a more effective strategy. It notes that for the state, it is economically advantageous to concentrate efforts and resources on different shelter types to return the homeless to independence rather than sustaining «chronic» homelessness. A crucial element is the incorporation of educational and vocational facilities into the structure of various shelters, providing the homeless with opportunities to receive education and acquire new skills. This contributes to their independent livelihood and integration into society. The article emphasizes the importance of not only providing various types of shelters but also creating conditions for the development of skills and independence among the homeless to achieve positive social impact. Goal. The aim of this article is to shed light on relevant types of shelters for homeless individuals, followed by an exploration of diverse initiatives and approaches aimed at addressing the issue of homelessness. Methodology. To establish patterns and characteristics of shelter typology for the homeless, an analysis of global and domestic design experience of such facilities was conducted, along with studying the research results of other scholars on the topic and reports from the Department of Social Policy. Social surveys of homeless individuals were also carried out. The results. This scientific research is a significant step in the detailed examination of practices related to providing services to the homeless in various projects. Special attention was given to types of shelters specializing in meeting the needs of different categories of homeless individuals. It is essential to consider aspects of organization and management of the aid and support system, including coordination efforts at various levels of government and local administration. The perspective includes studying the interaction between public and state institutions working in this field to develop an understanding of challenges and opportunities in this specific context. Scientific novelty. The article addresses the issue of homelessness in society. It underscores the need for a detailed analysis, especially studying the types of facilities that can be comfortable for different categories of individuals and highlights the best types that can facilitate the development of visitors to these establishments and provide them with independent living. This becomes particularly crucial in modern conditions, where the problem of homelessness is exacerbated by military conflict, demanding a deeper understanding of various aspects of this social phenomenon. Practical importance. The practical significance of different types of shelters for the homeless lies in their ability to provide specific services and support, such as temporary shelter for those who find themselves homeless, ensuring safety in crisis situations, medical and psychosocial assistance, skill development, professional training, educational programs, assistance in renting, and support in transitioning to permanent housing. Considering these aspects, various types of shelters become essential components of the social protection and rehabilitation system.